Islamic Financial Literacy in Muslim Majority Country - Irfan Syauqi Beik; Laily Dwi Arsyianti (ISLAMINOMICS: JOURNAL OF ISLAMIC ECONOMICS, BUSINESS AND FINANCE, 2020)
Various researches have been carried out by the most Muslims populous country in the world to identify the level of literacy towards Islamic economics and finance. The results showed that the literacy levels are still far below the target. This paper attempts to identify the programs that have been organized to increase the literacy level, the potential of human resources to lift up the level, as well as the research and development that have been and potential to be carried out in order to achieve much more level of literacy as targeted by the authority.